Phase 1 adaptive dose‐finding study of neoadjuvant gemcitabine combined with radiation therapy for patients with high‐risk extremity and trunk soft tissue sarcoma. Issue 20 (15th July 2015) - Tseng, William W.; Zhou, Shouhao; To, Christina A.; Thall, Peter F.; Lazar, Alexander J.; Pollock, Raphael E.; Lin, Patrick P.; Cormier, Janice N.; Lewis, Valerae O.; Feig, Barry W.; Hunt, Kelly K.; Ballo, Matthew T.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND This study was performed to determine the maximum tolerated dose (MTD) of gemcitabine given concurrently with preoperative, fixed‐dose external‐beam radiation therapy (EBRT) for patients with resectable, high‐risk extremity and trunk soft tissue sarcoma (STS). METHODS Gemcitabine was administered on days 1, 8, 22, 29, 43, and 50 with EBRT (50 Gy in 25 fractions over 5 weeks). The gemcitabine MTD was determined with a toxicity severity weight method (TSWM) incorporating 6 toxicity types. The TSWM is a Bayesian procedure that choses each cohort's dose to have a posterior mean total toxicity burden closest to a predetermined clinician‐defined target. Clinicopathologic and outcome data were also collected. RESULTS Thirty‐six patients completed the study. According to the TSWM, the gemcitabine MTD was 700 mg/m2. At this dose level, 4 patients (24%) experienced grade 4 toxicity; no toxicity‐related deaths occurred. All tumors were resected with microscopically negative margins. Pathologic responses of >90% tumor necrosis were achieved in 17 patients (47%); 14 (39%) had complete responses. With a median follow‐up of 6.2 years, the 5‐year locoregional recurrence–free survival, distant metastasis–free survival, and overall survival rates were 85%, 80%, and 86%, respectively. CONCLUSIONS The TSWM combines data from qualitatively different toxicities and can be used to determine the MTD for a drug given as part of a multimodality treatment. Neoadjuvant gemcitabine plus radiation therapy is feasible and safe in patients with high‐risk extremity and trunk STS. Major pathologic responses can be achieved, and after complete resection, long‐term clinical outcomes are encouraging. Cancer 2015;121:3659–3667. © 2015 American Cancer Society.